2002
DOI: 10.1111/j.1745-7599.2002.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioners' Treatment of Febrile Infants in Utah: Comparison to Physician Practice Nationally

Abstract: Management of a febrile infant is a common clinical scenario for the primary care provider. Although evidence-based protocols exist, the treatment of febrile infants remains controversial. Overall, NPs' evaluation and management of these infants were not shown to differ from physicians. Further studies are needed to determine why clinical guidelines are not being followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In a survey of 450 NPs regarding their treatment and management decisions in hypothetical case studies of febrile infants, NPs treated infants in a similar manner to physicians who were surveyed with the same questionnaire in a 1998 study (Badger, Lookinland, Tiedeman, Anderson, & Eggett, 2002). Badger et al, reported that physicians and NPs consistently ordered unnecessary tests and antibiotics for febrile infants, especially younger infants, despite current guidelines that recommended waiting and close follow‐up for suspected bacterial infection in this population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a survey of 450 NPs regarding their treatment and management decisions in hypothetical case studies of febrile infants, NPs treated infants in a similar manner to physicians who were surveyed with the same questionnaire in a 1998 study (Badger, Lookinland, Tiedeman, Anderson, & Eggett, 2002). Badger et al, reported that physicians and NPs consistently ordered unnecessary tests and antibiotics for febrile infants, especially younger infants, despite current guidelines that recommended waiting and close follow‐up for suspected bacterial infection in this population.…”
Section: Literature Reviewmentioning
confidence: 99%